E=mc² desmistificada: uma proposta de sequência didática para o ensino de física moderna com enfoque em suas aplicações - Vogt, Guilherme Guterres (2018)
Throughout our professional experience we realize that Modern Physics is a matter of great interest to our students. Bombarded daily with news that highlight technological advances can change the habits and customs of our society, the curiosity about the subject is without doubt, natural. Working these subjects in the classroom should also bring students closer to scientific knowledge and make physics teaching more accessible. This essay is the result of a two-year research, focusing mainly on the equation of mass and energy E = mc², giving rise to an educational product composed of a didactic sequence, which seeks to organize the environment around this equation and to direct the student to the expected result that will be the understanding of the presented concepts, as well as the meaning and the applications of the theme. It is organized giving theoretical foundation to the contexts of Physics and the Teaching area. We begin by structuring the concepts of Energy and Mass and later the conception and importance of the speed of light through what we call "Origins of the Equation". Also, to point out the results of researchers who identified in the theme great potential for Science, Technology and Society (CTS) and Significant Learning approach, areas of teaching in which we believe our work is inserted and allied to them the interdisciplinary potentiality that the product can be exploited jointly by teachers in the areas of Physics, Mathematics and Chemistry. Finally, it is an important tool for Physics Teaching, arousing great interest and curiosity in students, and in addition, the organization of this content resulted in topics that do not necessarily need to be worked in the established order and may rather, be used separately as theoretical complementation in specific classes.